MK-8776 and Olaparib Combination Acts Synergistically in Hepatocellular Carcinoma Cells, Demonstrating Lack of Adverse Effects on Liver Tissues in Ovarian Cancer PDX Model - Bębenek, Wiktoria; Gajek, Arkadiusz; Marczak, Agnieszka; Malý, Jan; Smejkal, Jiří; Statkiewicz, Małgorzata; Rusetska, Natalia; Bryś, Magdalena; Rogalska, Aneta (International journal of molecular sciences, 2025)
Hepatocellular carcinoma (HCC) cells critically depend on PARP1 and CHK1 activation for survival. Combining the PARP inhibitor (PARPi) olaparib with a CHK1 inhibitor (MK-8776, CHK1i) produced a synergistic effect, reducing cell viability and inducing marked oxidative stress and DNA damage, particularly in the HepG2 cells. This dual treatment significantly increased apoptosis markers, including γH2AX and caspase-3/7 activity. Both HCC cell lines exhibited heightened sensitivity to the combined treatment. The effect of drugs on the expression of proliferation markers in an olaparib-resistant patient-derived xenograft (PDX) model of ovarian cancer was also investigated. Ovarian tumors displayed reduced tissue growth, as reflected by a drop in proliferation marker Ki-67 levels in response to PARPi combined with CHK1i. No changes were observed in corresponding liver tissues using Ki-67 and pCHK staining, which indicates the absence of metastases and a hepatotoxic effect. Thus, our results indicate that the dual inhibition of PARP and CHK1 may prove to be a promising therapeutic approach in the treatment of primary HCC as well as OC tumors without the risk of liver metastases, especially in patients with olaparib-resistant tumor profiles.
Keywords: játra; nádory jater; Humans; Phthalazines; targeted therapy; Female; Drug Synergism; nádory vaječníků; Checkpoint Kinase 1; Ovarian Neoplasms; metastasis; lidé; PARP inhibitory; zvířata; proliferace buněk; myši; Liver Neoplasms; CHK1 inhibitor; Hep G2 Cells; synergismus léků; apoptóza; Mice; Poly(ADP-ribose) Polymerase Inhibitors; xenogenní modely - testy protinádorové aktivity; ftalaziny; ženské pohlaví; Liver; buňky Hep G2; olaparib; Cell Proliferation; ovarian cancer; piperaziny; checkpoint kinasa 1; nádorové buněčné linie; liver cancer; poškození DNA; DNA Damage; Xenograft Model Antitumor Assays; Piperazines; Animals; Cell Line, Tumor; replication stress; Apoptosis; Carcinoma, Hepatocellular; hepatocelulární karcinom